The Issues Of Metaphoric Competence Development On The Basis Of Literary Heritage - Saule Yerzhanova, Ruda Zaykenova, Bekzada Kozhekeyeva,; Jakypbekova, Mamilya; Mukasheva, Meruyert (Opción, 2019)
The aim of the study is to investigate the issues of metaphoric competence development on the basis of literary heritage via comparative qualitative research methods. As a result, a metaphor is a relationship between two concepts, one of which functions as the source and the other as the target at the conceptual level. In conclusion, in different cultures, metaphor may have different source domains that map onto the same target domain. Many complex conceptual metaphors reflect the various cultural models in that way.